Mission Theology 1948-1975 : Years of Worldwide Ceative Tension--Ecumenical, Evangelical, and Roman Catholic - Rodger C Bassham (Pasadena William Carey Library, 1979)
Presents the development of conservative evangelical mission theology as well as the tensions which accompany it.